Find the value of a 0 + a 1 + a 2 if
( 1 + 3 x + 4 x 2 ) 2 0 = a 0 + a 1 x + a 2 x 2 + . . . + a 4 0 x 4 0
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
( 1 + 3 x + 4 x 2 ) 2 0 = ( 1 + x ( 3 + 4 x ) ) 2 0 = 1 + 2 0 x ( 3 + 4 x ) + 2 2 0 × 1 9 x 2 ( 3 + 4 x ) 2 + ⋯ + x 2 0 ( 3 + 4 x ) 2 0 = 1 + 6 0 x + 8 0 x 2 + 1 9 0 x 2 ( 9 + 2 4 x + 1 6 x 2 ) + ⋯ + x 2 0 ( 3 + 4 x ) 2 0 = 1 + 6 0 x + 8 0 x 2 + 1 7 1 0 x 2 + ⋯ + x 2 0 ( 3 + 4 x ) 2 0 = 1 + 6 0 x + 1 7 9 0 x 2 + ⋯ + x 2 0 ( 3 + 4 x ) 2 0
⟹ a 0 + a 1 + a 2 = 1 + 6 0 + 1 7 9 0 = 1 8 5 1
Best solution for this will be like this.
Setting x=0, we get 1 = a 0 .
So a 0 = 1 .
Now for a 1 , differentiating the expression,
d x d ( 1 + 3 x + 4 x 2 ) 2 0 = 0 + a 1 + 2 a 2 x + . . . + n a n x n − 1
⟹ 2 0 . ( 1 + 3 x + 4 x 2 ) 1 9 . ( 3 + 8 x ) = a 1 + 2 a 2 x + . . n a n x n − 1 .
Set x = 0 for the expression we got,
⟹ 2 0 . ( 1 ) 1 9 . 3 = a 1
⟹ a 1 = 6 0 .
Again differentiating the differentiated expression, we will get,
2 0 [ 1 9 . ( 1 + 3 x + 4 x 2 ) 1 8 . ( 3 + 8 x ) + 8 . ( 1 + 3 x + 4 x 2 ) 1 9 = 0 + 0 + 2 a 2 + 3 . 2 a 3 x + . . .
Setting x=0, and then solving for a 2 we get a 2 = 1 7 9 0 .
So a 0 + a 1 + a 2 = 1 8 5 1
Hey , bro did the same and yes its the best ⌣ ¨ . Btw, triple boxed doesn't look nice :P (LOL) (+1)
Problem Loading...
Note Loading...
Set Loading...
Clearly a 0 = 1 , and a 1 = 3 ⋅ 2 0 = 6 0 . There are two ways to get x 2 in the expansion: two copies of 3 x and eighteen of 1 , or one copy of 4 x 2 and nineteen of 1 . The former adds up to 9 ( 2 2 0 ) x 2 and the latter adds up to 4 ⋅ 2 0 x 2 , so the sum is 1 7 9 0 x 2 . Thus the answer is 1 + 6 0 + 1 7 9 0 = 1 8 5 1 .
(If you wanted, you could also use Taylor series.)